A prototype system for generating lesson plans for secondary school teachers - Tan, Choon Keong (Penerbit UMS, 2022)
The Ministry of Education (MOE) Malaysia directed that every teacher of secondary schools is responsible to prepare lesson plan for each lesson when teaching in a class. The paper reports the use of a prototype system by school teachers to produce digital lesson plans. The system was developed utilising the ADDIE Model. Five teachers from Kian Kok High School, Kota Kinabalu, Sabah was selected to test-run the system. The results of the interview were analysed in a qualitatively way. The findings showed that all the 5 subjects agreed the system was able to function smoothly to create digital lesson plans. Many other functions were tested and also reported to be successful. There were many challenges were reported by the subjects but the researcher was only managed to attend to some of them due to financial constraints of the grant. The research concluded that lesson plans generator that is reliable and effective must be in the online mode in the future so that users can access more teaching resources.